Collaborative Writing on Google Docs: Effects on EFL Learners’ Descriptive Paragraphs - Valizadeh, Mohammadreza (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
Google Docs has recently been suggested as an efficient collaborative tool for group writing. This experimental quantitative study, including pretest-treatment-posttest design, aimed at comparing the effects of collaborative writing on Google Docs and individual writing practice on EFL learners’ descriptive paragraphs. The participants were 48 Turkish EFL learners at pre-intermediate level of proficiency, based on their performance on Oxford Placement Test. The participants were assigned to two groups. One group, including 24 participants, experienced collaborative writing on Google Docs plus researchers’ comments as feedback (CWGD group). The other group, including 24 participants, experienced individual writing practice plus researcher’s direct corrective feedback (IWP group). The results of the independent samples t-test indicated that the CWGD group significantly outperformed the IWP group. In conclusion, collaborative writing Google Docs environment can enhance the writing skill of the EFL learners. Therefore, the study highly recommends utilizing collaborative writing on Google Docs to practice English language writing skill.